Early Child Education Based on Islamic Psychology - Devy Habibi Muhammad; Agustiriani Eka Desari (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study aims to explain early childhood education based on Islamic psychology, a study approach to understanding child psychology and behavior based on monotheism through the integration of science and faith. Islamic psychology is a form of psychology based on the description of humans, especially in Islam, who have different uniqueness. The formulation of the problem in this research is how early childhood Islamic education tells Islamic psychology. This research is a study that uses literature sources to obtain research data. This study's results provide a new view that is different from contemporary western psychology. Islamic psychology emphasizes the need to keep the child's soul closer to Allah, the creator. A person whose soul is open will be wiser, more compassionate, and more understanding than those whose soul is closed. The soul referred to here is the inner spiritual nature, not the soul in the physical sense. The soul is the source of inner light, inspiration, creativity, and compassion. The concept of understanding that individual consists of some unique behavior and spirit, and these factors are closely related and essential for the success of the learning process.